A study of some factors affecting the mortality rate in diffuse peritonitis. Issue 4 (December 1963) - Dawson, J. L.
Abstract : The results of a retrospective analysis of the records of 665 consecutive patients with diffuse peritonitis emphasize the considerable effect age and causal lesion have on the prognosis. The comparison of results of any innovations in the treatment of diffuse peritonitis cannot be assessed unless these factors are fully taken into account. The fallacy of comparing overall mortality figures is demonstrated. The high mortality rate for diffuse peritonitis associated with diverticulitis is noted.